Graphene oxide: A glimmer of hope for Assisted Reproductive Technology. (September 2019) - Ramal-Sanchez, Marina; Valbonetti, Luca; Tsikis, Guillaume; Dubuisson, Florine; Blache, Marie-Claire; Labas, Valerie; Druart, Xavier; Fontana, Antonella; Mermillod, Pascal; Barboni, Barbara; Saint-Dizier, Marie; Bernabo, Nicola
Abstract: Infertility is a worldwide problem affecting around 48.5 million couples in the word, the male factor being responsible for approximately the 50% of the cases, with a high percentage of unknown causes. For that reason, improving the success of In Vitro Fertilization (IVF) techniques is a primordial aim for researchers working in the reproductive field. Here, by using a mammalian animal model, the bovine, we present an innovative in vitro fertilization system that combines the use of a somatic component, the epithelial oviductal cells, and a carbon-based material, the graphene oxide, with the aim to open new ways in IVF systems design and application. Our results show an increase in the IVF outcomes without harming the blastocyst developmental rate, as well as high modified proteomic and lipidomic profiles of capacitating spermatozoa. Furthermore, we compared the modifications produced by GO with those exerted by the hormone progesterone, finding similar functional effects on sperm capacitation. In conclusion, our results stand out the use of a non-physiological material as graphene oxide in a new and innovative strategy that improves sperm capacitation, conferring them a higher fertilizing competence and thus increasing the in vitro fertilization outcomes. Graphical abstract: Image 1